2019
DOI: 10.1016/j.engstruct.2019.109687
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human-structure interaction on a lively lightweight GFRP footbridge

Abstract: Human activities and occupancy can induce excessive structural vibrations. Human-structure interaction (HSI) can significantly affect responses. However, this phenomenon is not accounted for in many design guidelines due to lack of experimental studies. Concurrently, there is increasing application of lightweight high-strength materials such as glass fibre reinforced polymer (GFRP). The vibration sensitivity of such structures is not yet well known, despite the expectation that it could be important due to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Different from the HSI on footbridges, 36,37 the walking directions of pedestrians are diverse on the composite floor. To research the above problem, the following combinations of walking directions (as shown in Figure 8) are considered.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Different from the HSI on footbridges, 36,37 the walking directions of pedestrians are diverse on the composite floor. To research the above problem, the following combinations of walking directions (as shown in Figure 8) are considered.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Accurate estimation of human-induced vibration in footbridges may also require taking HSI into account [4,27,28]. In the modeling of HSI, the human body in a walking posture is usually modeled as a SDoF mass-damper-spring system [4,[29][30][31][32].…”
Section: Parameter Mean Value Covmentioning
confidence: 99%
“…Furthermore, due to the low weight of the GFRP web-core footbridges, the non-structural mass of pedestrians on the bridge deck will play an important role in the overall vibration behaviour of the footbridge. Human-structure interaction [28][29][30][31][32] is a well-known phenomenon in which the dynamics of the two subsystems interact and they start to influence each other. Due to this interaction, certain dynamic properties, i.e.…”
Section: Introductionmentioning
confidence: 99%